Krytyka cywilizacji naukowo-technicznej Zachodu w eko-filozofii Henryka Skolimowskiego - Murzyn, Marcin (Studia Europaea Gnesnensia, 2023)
Polish philosopher and ecologist Henryk Skolimowski developed the paradigm of eco-philosophy, which is critical of the scientific and technical civilization. According to Skolimowski, the latter tends towards mindless expansion and exploitation of the natural environment, which results in the destruction of ecosystems and threatens future generations. The philosopher proposes replacing that culture with another one, based on the principles of sustainable development, harmonious cooperation with nature and respect for cultural and biological diversity. Skolimowski highlights the need to change the mindset and approach to the world in order to provide future generations with a healthy and sustainable living environment.